Lysine and dried whey additions in starter pig diets - D S Pollmann; G A Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1982)
A total of 943 newly weaned (18 to 30 days of age) pigs were used in five trials to evaluate the addition of lysine and dried whey in starter diets. The results of these studies show that the lysine requirement is 1.2 to 1.3% during the nursery phase (up to approximately 50 lbs). When lysine levels are greater than 1.3% with added L-Iysine monohydrochloride, a reduction in performance will be evident (P<.05). Rolled dried whey appears to be inferior (P<.10) to spray dried whey in starter pig diets.; Swine Day, Manhattan, KS, November 11, 1982
Keywords: Swine day; 1982; Kansas Agricultural Experiment Station contribution; no. 82-614-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 422; Swine; Lysine; Starter pig; Dried whey